An analysis of New Zealand suicide attempts in 1980-1988 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Statistics at Massey University, New Zealand - Tan, Ming Yik (Massey University, 1991)
Suicide attempts have been of concern throughout the world especially in youths so that a study of the distribution of these acts is important and necessary. The aim of this thesis is to study the influence of certain demographic variables on suicide attempts. The New Zealand Morbidity Data were merged with Population Census Data to obtain frequencies and rates of suicide attempts for subgroups of the population. The data were displayed in different ways to find the affect of various demographic variables such as sex, age, race, method of attempt, length of stay in hospital and geographical area. These variables were examined singly and jointly to reveal possible interactions. The graphs and tables produced provided some confirmation of trends noted in the literature, namely that attempts were high for females and for adolescents but males tend to dominate the cases of successful suicide. Reasons for these differences are explored. This study did not confirm the belief that suicide attempts are correlated with population density. The influence of time of year was examined and there was shown to be a trend of increased attempts in the warmer months. The two sets of morbidity data, 1980 and 1988, enabled comparisons to be made over time.
The Author
Keywords: Suicide; Psychological aspects; Social aspects; New Zealand; Research Subject Categories::MATHEMATICS::Applied mathematics::Mathematical statistics